Efficient and cost-effective dye-sensitized solar cells using MWCNT-TiO2 nanocomposite as photoanode and MWCNT as Pt-free counter electrode. (August 2019) - Younas, M.; Gondal, M.A.; Dastageer, M.A.; Harrabi, K.
Graphical abstract: Highlights: Novel [ n -MWCNT-TiO2 /N3/MWCNT] DSSC configuration was proposed and fabricated. Conventional Pt based counter electrode was replaced by inexpensive MWCNT. Different mass ratios of MWCNT-TiO2 nanocomposites were used as photoanode. Proposed MWCNT DSSCs were found to be more efficient than Pt based DSSCs. The efficiency as high as 7.15% is observed in [0.06%-MWCNT-TiO2 /N3/MWCNT]. Abstract: In the present study, a new cost-effective and efficient configuration [ n -MWCNT-TiO2 /N3/MWCNT] of dye-sensitized solar cell (DSSC) is proposed and fabricated, where n -MWCNT-TiO2 is the nano composite of multiwall carbon nanotube (MWCNT), and titanium dioxide (TiO2 ) in different mass proportions, sensitized by N3 dye used as a photo anode, and MWCNT is the material for the counter electrode. In the [ n -MWCNT-TiO2 /N3/MWCNT] configuration, the photo anode with four mass proportions ( n  = 0.03%, 0.06%, 0.09% and 0.12%) were used as a design variant, and it was found that the photovoltaic efficiency as high as 7.15% was achieved when the nano composite of 0.06%-MWCNT-TiO2 was applied as a photoanode in the proposed DSSC configuration. Besides achieving a 13% photovoltaic efficiency enhancement compared to the ubiquitous [TiO2 /N3/Pt] DSSC configuration, the replacement of Pt with inexpensive MWCNT in the [ n -MWCNT-TiO2 /N3/MWCNT] DSSC ensures the cost effectiveness of the proposed configuration. The morphological and optical characterization of the n- MWCNT-TiO2 photoanode (nanocomposite) films, the stability and catalytic activity of MWCNT counter electrode, UV–VIS absorption spectroscopy, current-voltage characteristics, incident photon to electron conversion efficiency and the electrochemical impedance spectroscopy of the fabricated DSSCs were performed in order to elucidate the improved performance of the [ n -MWCNT-TiO2 /N3/MWCNT] configuration. Based on these characterization studies, it was found that the observed enhancement of light absorbance in the visible spectral region, the improved electron transportation, decreased recombination of electrons with oxidized dye and redox mediator, better catalytic activity of MWCNT counter electrode are the key contributory factors for the increased photovoltaic efficiency of the [ n -MWCNT-TiO2 /N3/MWCNT] DSSC configuration.